Virtually managing (in)visibility: Girls, social media, and rural U.S. family relationships - Rickman, Aimee (AoIR Selected Papers of Internet Research, 2013)
Drawing upon data from a year-long ethnographic study involving 15 rural female U.S. teens, this paper uses critical theory and queer theory to explore how Facebook and Twitter use influences and is influenced by young women’s experiences within family. Findings suggest interlocutors use social media to “get around” ideological and physical constraints to involvement they face as minors and females in families. Living in social media, interlocutors reported they strategically perform social identities to enhance the visibility of traits encouraging parental trust and connection. At the same time, they used these platforms together to perform invisibility, allowing them to quietly subvert certain parental controls that police and restrict their involvements offline.